PENERAPAN STRUKTUR 8 BABAK PADA NASKAH FILM RERANTIG SENJA DI RUMAH PRODUKSI CV. LUAR KOTAK AUDIOVISUAL - Effendi, Daffa Nabawi; Prabhawita, Gede Basuyoga; Putra, Ida Bagus Hari Kayana (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
Kampus Merdeka is a policy initiated by the Indonesian Ministry of Education and Culture that allows students to develop interdisciplinary skills, one of which is through the Merdeka Belajar Kampus Merdeka (MBKM) program. In this final report, the author collaborated with Luar Kotak Audiovisual to develop an independent project in the form of a fictional film script titled RERANTING SENJA. This final project discusses the process of creating a fictional film script entitled Reranting Senja, which highlights themes of self-recovery after loss, emotional pressure, and identity exploration. The story centers on the main character, Raka, a photographer experiencing an existential crisis following the death of his father and the emotional strain in his relationship with his partner, Laras. The project adopts the Eight-Sequence Structure (Elizabeth Lutters) as the narrative framework. This structure is used to shape the emotional transitions of the character gradually and dynamically, from the initial set-up, internal conflict, to a resolution that touches both psychological and spiritual aspects. The creative process began with the exploration of themes such as grief and relational tension, which were visualized through elements like photography, silent spaces, and symbols of familial memory. The scriptwriting adopts a character-driven approach, where the narrative development is shaped by the protagonist’s internal conflicts. Elements such as reflective dialogues, still visuals, and dramatic rhythm are used to deepen the atmosphere and evoke emotional responses from the audience. The final result is a fictional script with a duration of approximately 90 minutes, consisting of 28 major scenes that represent the transformative chapters of Raka’s journey. Through Reranting Senja, the author attempts to portray that healing is not about returning to who we once were, but about becoming someone new. This work aims to reflect on mental health issues and the importance of healthy relationships in one’s life, while also contributing to the development of more psychologically and emotionally nuanced screenplay writing.